Staphylococcus aureus β-hemolysin impairs oxygen transport without causing hemolysis - Qi Li; Nan Chen; Chenghua Liu; Zhen Zhao; Minjun Huang; Jingjing Li; Guang Yang (Virulence)
Staphylococcus aureus (S. aureus) infection can lead to the occurrence of hypoxia, however, the underlying mechanisms have not been fully elucidated. β-hemolysin (Hlb) induced hemolysis of red blood cells (RBCs) requires a temperature transition from “hot” to “cold,” a phenomenon not observed under physiological conditions. In this study, we discovered that RBCs treated with Hlb exhibited a high level of intracellular Ca2+ and underwent a shape transformation from biconcave discoid to spherical, which was contingent upon the degradation of sphingomyelin of the cell membrane and led to impaired oxygen transport. The increase in intracellular Ca2+ levels induced by Hlb was dependent on the activation of the ion channel N-methyl-D-aspartate receptor. Furthermore, we found that Hlb-induced Ca2+ influx increased the cytoplasmic pH and subsequently attenuated the oxygen release from RBCs, which were also observed in both hlb transgenic mice and a murine model with S. aureus challenge. Our findings reveal a novel role for Hlb as sphingomyelinase in impairing RBC function under non-lytic conditions, shedding light on the mechanism behind hypoxia associated with S. aureus infection.